Universal health care delivery mitigates socioeconomic-related risk for adverse outcomes in hospitalised patients: Lessons from the COVID-19 pandemic in Australia. - Fahimeh Faqihi; Rita Perri; Jimmy Chien; Jin-Gun Cho; Stephen Milne; Shopna Bag; Nicole Gilroy; John R Wheatley; Kristina Kairaitis (PLoS ONE)
Background Internationally, socioeconomic disadvantage is related to severe outcomes of COVID-19. We investigated the impact of socioeconomic disadvantage on infection rates, hospitalisation, and in-hospital outcomes for COVID-19 with standardised medical care. Methods This retrospective cross-sectional study included SARS-CoV-2 PCR-confirmed patients ≥18 years, admitted to a major public hospital between January 2020 and December 2021. Severe COVID-19 outcomes were defined by a composite outcome of in-hospital death or other critical complications. A generalised linear regression model of demographic features, co-existing conditions, and socioeconomic status was used to determine the risks of the composite outcome. Results Of 797,343 individuals ≥18 years in the health district, 50,906 (6.4%) were PCR-positive, and 1,962 were hospitalised. Compared with the whole health district population, infected individuals were younger (median [interquartile range] age 35 [25-48] years vs 42 [31-58] years) and from areas with the greatest socioeconomic disadvantage (34.4% vs 20%; both p < 0.0001). Hospitalised patients were older, with more females compared to the PCR-positive group (46 years [33-61], 53.5%, respectively; p < 0.001), and 51.2% were from postcodes with greatest socioeconomic disadvantage (p < 0.0001). The composite outcome occurred in 11.5%, with an in-hospital mortality of 3.8%. Higher risk of the composite outcome was observed in males (OR 1.72, 95% CI [1.26-2.42], p < 0.001), patients aged ≥ 65 years (OR 6.96, [3.3-14.6], p < 0.001), those with ≥ 4 comorbidities (OR 2.67, [1.54-4.63], p < 0.001), and unvaccinated patients (OR 1.57, [1.05-2.38], p < 0.05). The risk of composite outcome did not increase with socioeconomic disadvantage (OR 0.97, [0.68, 1.42], p = 0.64). Conclusion In the absence of capacity restraints, socioeconomic disadvantage was not associated with severe in-hospital outcomes in a well-resourced care environment despite increased rates of infection and hospitalisation. This highlights the impact of universally accessible, standardised, protocolised, high-quality in-hospital care in reducing the risk of adverse in-hospital outcomes in socioeconomically disadvantaged patients.